Heritage-based education and what it means to private universities in Zimbabwe - Ephias Gudyanga; Erick Nyoni (S&Co Publishing, 2025)
The study on Heritage-based education and what it means to private universities in Zimbabwe was informed by the Transformative Continuity theory. A mixed methods approach was used to gather data from four lecturers in three private universities. An intense open-ended questionnaire was used as an instrument for data collection from a convenient sample of lecturer-participants. Two research questions were formulated: How are private universities aligning themselves for value addition as local industry solution providers? What interventions can be implemented to ensure Zimbabwean private universities are capacitated to subscribe fully to Education 5.0? Thematic data analysis techniques were used and it was found that private universities are not aligning themselves for value addition as local industry solution providers. Private universities are fully aware of what is to be done as far as Heritage Based Education 5.0 is concerned, however, resources and lack of motivation impact negatively. Availability of resources, further awareness of the heritage-based education philosophy, and a futuristic culture bias towards technology are some of the interventions that can be put in place to ensure that Zimbabwean private universities are capacitated to subscribe fully to Education 5.0. As informed by the transformative continuity theoretical model as a lens to our study, we concluded that by applying Heritage Based Education, private universities have the potential for carrying out innovative research, leading to the production of goods and services; therefore, having the potential to transform Zimbabwe’s disturbed economic system.